IMPLEMENTASI PERMENDIKBUD RISTEKDIKTI No. 24 TAHUN 2022 DALAM MENINGKATKAN MINAT PENGUNJUNG MUSEUM DR. MUHAMAD SALEH KOTA PROBOLINGGO - Siti Aisyah (POPULIKA, 2025)
This study aims to evaluate the implementation of Ministry of Education, Culture, Research, and Technology Regulation No. 24 of 2022 in increasing public interest in visiting the Dr. Mohamad Saleh Museum in Probolinggo City. A descriptive qualitative method was employed, supported by quantitative SWOT analysis to identify the strengths, weaknesses, opportunities, and threats associated with the policy’s execution. The findings indicate that the regulation has positively contributed to strengthening the museum’s educational function. However, its implementation still faces several obstacles, such as limitations in human resources, restricted operational funding, and underdeveloped promotional and digital initiatives. The SWOT analysis places the museum’s development strategy in the Strength–Opportunity (SO) quadrant, suggesting that internal strengths can be utilized effectively to capitalize on external opportunities. Recommended strategies include digitizing the museum’s collections to enhance public access, fostering collaboration with educational institutions, and developing curriculum-based educational programs. In addition, leveraging social media and other digital platforms is considered essential to reach younger audiences and increase the museum’s visibility. This study recommends the importance of synergy between local government, museum management, and educational institutions to strengthen the museum’s role as a center for education and local culture. In the context of the digital era, such collaboration is crucial for maintaining the museum’s relevance and competitiveness within the broader community. Keywords: Policy Implementation; Regional Museum; Visitor Engagement; SWOT Analysis; Digital Transformation